Very-Low-Dose Levodopa Therapy for Pediatric Neurological Disorders: A Preliminary Questionnaire in Japan - Hoshino, Kyoko; Hayashi, Masaharu; Ishizaki, Asayo; Kimura, Kazue; Kubota, Masaya; Nezu, Atsuo; Yasuhara, Akihiro (Frontiers in Pediatrics, 2021)
Introduction: Postsynaptic dopamine receptor supersensitivity (DARSS) has been extensively researched by Dr. Masaya Segawa, who has investigated the efficacy of very-low-dose levodopa therapy (VLDT; 0.5-1 mg/kg/day). Considerable Japanese research supports the possibility that VLDT could be used to treat pediatric neurological disorders. We conducted an on-line survey in 2014 to collect real-world data on the use of VLDT to treat DARSS. Methods: A two-step survey, including a screening test and questionnaire, was posted on a private internet site that could be accessed via the VLDT Research Group home page, and 1165 pediatric neurologists across Japan were invited to complete it. Results: A total of 25 respondents reported prescribing VLDT; 19 used VLDT to treat autism spectrum disorder, 14 for tics, 12 for speech delay, 9 for Rett syndrome, 7 for attention-deficit/hyperactivity disorder, intellectual disability, and 6 for sleep problems. Twelve respondents reported prescribing a dose of 0.5 mg/kg. Twenty-two reported that VLDT was effective for treating behavioral problems, and twenty reported a good efficacy for treating motor symptoms. Adverse events had a low incidence. Notably, respondents chose VLDT for its possible action in DARSS and for its safety. VLDT was commonly used for behavioral problems in patients younger than 5 years, and for motor symptoms in aged 5-9 years. Conclusion: VLDT could safely treat behavioral and motor symptoms in pediatric neurological disorders. In contrast, dopamine antagonists are associated with potent efficacy, but with adverse effects such as sleepiness and obesity. Further surveys should be conducted with a broader participants.